A Validity and Effectiveness PBL-Based Dilemma Story E-Module Colloid Topic to Improve Critical Thinking Ability - Rima, Rima Yanti; Almubarak; Iriani, Rilia (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2024)
The ability to think critically is one of the competencies needed in 21st-century education. In addition to the role of teachers in improving critical thinking skills, of course, the teaching materials used must also support in improving the critical thinking skills of students. This research is an R&D research with the development model used as a 4D model consisting of 4 phases 1) define, 2 ) design, 3) development, and 4) disseminate. Development in the form of teaching materials for PBL-based dilemma story e-modules on colloidal materials aims to produce valid, practical, and effective learning materials. The results showed that the developed e-modules met the feasible criteria with valid, practical, and effective indicators. The conclusion is that the teaching material for the PBL-based dilemma story e-module is a means for teachers and especially students to improve critical thinking skills.